2004
DOI: 10.1093/bja/aeh119
|View full text |Cite
|
Sign up to set email alerts
|

Skin blood flow and plasma catecholamine concentrations during removal of a phaeochromocytoma in a child

Abstract: A 9-yr-old boy with an adrenal phaeochromocytoma underwent removal of the tumour under general anaesthesia using sevoflurane and nitrous oxide combined with thoracic epidural anaesthesia. Skin blood flow in the first toe, as measured by laser Doppler flowmetry, markedly decreased during manipulation of the tumour and increased after removal of it. Skin blood flow correlated more significantly with plasma catecholamine concentrations than did mean arterial blood pressure. Skin blood flow may be used as a non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…[135810] Significant negative correlation between plasma catecholamine concentration and skin blood flow has been demonstrated in pheochromocytoma. [1011] Resolution of ischemia and wound healing after removal of pheochromocytoma confirms the suggestion that excess catecholamine was responsible for the development of critical toe ischemia in our patient.…”
Section: Discussionsupporting
confidence: 85%
“…[135810] Significant negative correlation between plasma catecholamine concentration and skin blood flow has been demonstrated in pheochromocytoma. [1011] Resolution of ischemia and wound healing after removal of pheochromocytoma confirms the suggestion that excess catecholamine was responsible for the development of critical toe ischemia in our patient.…”
Section: Discussionsupporting
confidence: 85%
“…Phaeochromocytoma rarely presents with acute limb ischaemia [5, 6]. Significant negative correlations between plasma catecholamine concentration and dermal blood flow have been demonstrated in patients with phaeochromocytomas [7]. Hence, chronic recurrent arterial vasospasm, due to excessive catecholamine production from phaeochromocytoma, was likely to have caused scleroderma-like features of our patient's hands, with blanching due to surges of catecholamine production and sustained elevation leading to pulp atrophy and skin tightening.…”
Section: Discussionmentioning
confidence: 89%
“…Russell et al [13], in a retrospective analysis of a group of adult patients, found a significant correlation between intraoperative cardiovascular instability and peak serum catecholamine levels measured at the time. Mikasa et al [14] also showed a significant correlation between plasma norepinephrine concentration and mean arterial pressure during surgery. Bryskin and Weldon [15] reported that the infusion of dexmedetomidine and magnesium sulfate in their case was effective for stable hemodynamics, with the pattern of steadily decreasing catecholamine levels following intubation.…”
Section: Discussionmentioning
confidence: 98%